Development and structure activity relationship of diarylpentadienone and chalcone analogues as potential anti-inflammatory agent - Mohd Faudzi, Siti Munirah (2015)
The main adverse effects of current non-steroidal anti-inflammatory drugs (NSAIDs), involved the gastroinstestinal tract, kidney and blood clotting has lead to the discovery of new drugs with improved safety profile today. Curcumin could be serves as potential NSAID candidate based on its strong anti-inflammatory property and low toxicity. However, its utilization in clinical trials was restricted due to poor pharmacokinetic properties. Thus far, several modifications of curcumin structure have been conducted, and reports have shown that diarylpentanoid scaffold without the β-diketone moiety influenced their anti-inflammatory properties via nitric oxide (NO) production suppression activity and inhibition on pro-inflammatory cytokines such as tumor necrosis factor alpha (TNF-α) and interleukin-6 (IL-6). In this study, a series of forty-five curcumin like compounds, the 1,5-diphenylpenta- 2,4-dien-1-ones and five pyrazoline-diarylpentadienone analogues were synthesized following the Lipinski rule, and evaluated for nitric oxide (NO) suppression activity on interferon gamma (IFN-γ)/ lipopolysaccharides (LPS)-activated RAW 264.7 cells. Among these, compounds 3h, 7a, 7d, and 7e exhibited comparable or significantly enhancing anti-inflammatory property compared to curcumin (IC50 = 14.69 ± 0.24 μM), of which compound 7d (5-methyl-thiophene bearing) displayed the most promising NO inhibitory activity with IC50 value of 10.2 ± 0.6 μM. In order to understand the structure-activity relationship (SAR) to the bioactivity, twodimensional (2D) and three-dimensional (3D) quantitative structure activity relationship (QSAR) studies were carried out. The structure activity relationship (SAR) study revealed that para-hydroxyl group on ring B, and either meta-hydroxy or para-hydroxy moieties on ring A are crucial for a remarkable anti-inflammatory activity. Based on absorption, distribution, metabolism, excretion and toxicity (ADMET) and toxicity prediction by computer assisted technology (TOPKAT) analyses, compounds 1c (IC50 = 26.1 ± 0.1 μM) is predicted to have a good solubility and absorption, non-mutagenic and to exhibit high blood−brain barrier (BBB) penetration, which indicates a potential as an effective drug candidates for treating the central nervous system (CNS) related disorders. Due to impressive array of biological profiles of pyrrole and chalcone, we therefore adopted the pyrrole structure and fused it into chalcone scaffold by replacing one of the aromatic rings, in an attempt to develop a new series of chalcone analogues with higher anti-inflammatory potential. All nine synthesized compounds displayed nitric oxide (NO) production suppression effect with IC50 values ranging from 21.5 to 62.9 μM. Among them, compounds 9c (2,5-dimethoxy containing compound) and 9h (2- methoxy bearing compound) exhibited highest nitric oxide (NO) inhibition effect with IC50 values of 21.5 ± 0.6 μM and 21.6 ± 1.1 μM, respectively.